Socialization of the Effect of Work Discipline on Employee Performance: A Mediation Study of Motivation as an Intervening Factor at the Regional Revenue Office of Medan City - Waruwu, Ahmad Aswan (Yayasan Rahmat Islamiyah, 2026)
Work discipline is one of the key factors in improving employee performance within government institutions. However, performance improvement is influenced not only by discipline but also by motivation as an intervening variable. This Community Service Program (PKM) aims to socialize the influence of work discipline on employee performance by positioning motivation as a mediating factor at the Kantor Dinas Pendapatan Kota Medan in Medan. The methods employed in this program include counseling sessions, interactive discussions, and the delivery of case-based materials relevant to the employees’ working conditions. The results of the activity indicate an increased understanding among employees regarding the importance of work discipline and motivation in supporting productivity and improving the quality of public services. Furthermore, participants were able to identify sustainable strategies for enhancing discipline and work motivation. This program is expected to make a tangible contribution to improving employee performance and supporting the realization of effective, efficient, and professional governance.